Multi-Response Optimization of Safety Conformity using Taguchi Scheme in a Bottling Process Plant - Shedrach Aliakwe Martins; Sunday Ayoola Oke (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2021)
Previous research has examined safety conformity in process plants in terms of machine guarding guideline compliance behavior of operators. However, it is not clear how the safety conformity of workers in non-equipment related activities could be evaluated. This paper proposes a new Taguchi based method to optimize the safety conformity of workers in equipment and non-equipment related activities in a bottling process plant. The unique elements of the paper are the introduction of global and specific value determination mechanisms for the process. The validity of the procedure was ascertained by field data from a developing country. The results obtained revealed that the conformity of the work to safety procedures leads to a healthy state of operation in the industry. The study’s outcome may benefit the safety manager in the organization by raising conformity awareness among workers and enhances safety budget planning with information obtained from the methodology.